Assessment of dietary supplementation of green iron oxide nanoparticles: impact on growth performance, ammonia emissions, carcass criteria, tissue iron content, and meat quality in broiler chickens under hot climate conditions - Almeldin, Yousri A. R.; Eldlebshany, Amira E.; Elkhalek, Enass Abd; Lohakare, Jayant; Abdel-Wareth, Ahmed A. A. (Frontiers in Veterinary Science, 2024)
The potential significance and importance of green iron nanoparticles (Nano-Fe) in poultry production lie in their capability to effectively tackle iron deficiency in poultry. Iron, an indispensable mineral for numerous physiological functions in birds, such as oxygen transport, energy metabolism, and immune response, underscores the critical need for adequate iron levels. Nevertheless, conventional iron supplementation methods frequently face hurdles like limited bioavailability rates in poultry. To enhance performance, and promote sustainable broiler productivity, Nano-Fe showed promise as an efficient feed supplement for broiler chickens. The objective of this study was to assess the impact of green Nano-Fe inclusions in diets on growth, ammonia excretion, carcass criteria, and meat quality in broiler chickens. A total of 192 one-day-old male Ross 308 broiler chicks, were assigned to three treatment diets including Nano-Fe oxide at 0, 20, or 40 mg/kg, respectively, for 42 days. Each treatment comprised eight replicates, each with eight broiler chicks. Two phases comprised the 42-day study (0 to 21 days for the starter and 21 to 42 days for the finisher).In comparison to the control group, the Nano-Fe oxide groups 20 mg/kg and 40 mg/kg linearly improved (P < 0.05) body weight (R 2 =0.574) and body weight gain (R 2 =0.367) under hot climatic conditions at 42 days of age. Furthermore, Nano-Fe oxide to broiler diets, improved (linear, P < 0.05) feed conversion ratio (R 2 =0.424) throughout whole periods. The ammonia content of excreta (R 2 =0.454) was linearly decreased (P < 0.05) with increasing Nano-Fe oxide levels in broiler diets compared to control at 21 and 42 days of age. Nano-Fe oxide positively influences cook loss, water-holding capacity, and iron content in various tissues. Moreover, it contributes to a healthier carcass yield and reduced abdominal fat. In conclusion, broiler chickens fed diets containing Nano-Fe oxide at 20 mg/kg and 40 mg/kg demonstrated enhanced growth performance, improved meat quality, increased iron content in tissues, dressing percentage, and reduced abdominal fat deposition. Future research should explore the impact of green Nano-Fe oxide on additional factors such as the microbiome and gene expression related to immunity and heat stress.